Formulation of infant formula with different casein fractions and their effects on physical properties and digestion characteristics. Issue 2 (24th December 2021) - Zhang, Junpeng; Du, Xinyu; Jiang, Shilong; Xie, Qinggang; Mu, Guangqing; Wu, Xiaomeng
Abstract : This study investigated whether casein (CN) fractions exhibit better physical properties and digestibility than native casein micelles presently used in the production of infant formula. Abstract : This study investigated whether casein (CN) fractions exhibit better physical properties and digestibility than native casein micelles presently used in the production of infant formula. The structural performance of native casein micelles (micellar casein concentrates, MCC), β-CN, κ-CN and β + κ-CN were explored, and physical properties and digestion characteristics ( i.e., digestibility, particle size, zeta potential and microscopic morphology) of the infant formula with MCC, β-CN, κ-CN or β + κ-CN were determined to elucidate the applicability of these casein types in infant formula. Results indicated that the β + κ-CN infant formula solution had the largest particle size with the most unstable potential. Moreover, both β-CN and κ-CN infant formula showed high solubility, while κ-CN displayed the lowest foaming capacity and high foaming stability. β-CN infant formula expressed an effective digestibility property, however, it possessed the largest particle size after gastrointestinal digestion. Therefore, β-CN fraction infant formula showed better digestibility than casein infant formula, and thus this work provides a theoretical basis for the development of infant formula.